APPROXIMATE SOLUTION FOR BURGER'S-FISHER EQUATION BY VARIATIONAL ITERATION TRANSFORM METHOD - Ali Al-FAYADH (Tikrit Journal of Pure Science, 2018)
Nonlinear partial differential equations represent the most important phenomena occurring in the world and are encountered in various fields of science. Generalized Burger’s-Fisher equation is very important for describing different mechanisms. Burger’s-Fisher equation arises in the field of applied mathematics and physics applications. This equation shows a prototypical model for describing the interaction between the reaction mechanisms, convection effect, and diffusion transport. In this paper, variational iteration transform method that combines Laplace transform and the variational iteration method, which  used to obtain approximate analytical solutions of Burger’s - Fisher equation. Comparison of the results obtained by the present method with the exact solution and other existing methods reveals the accuracy and fast convergence of the proposed method.